Digital Accessibility of Educational Information Content Taking into Account the Web Content Accessibility Guidelines - E. S. Piskun; U. A. Maksimchuk (Цифровая трансформация, 2025)
The importance of developing educational web content for users with disabilities, in particular, visual, hearing, motor and cognitive impairments, is shown. Legislative norms and key principles of Web Content Acces sibility Guidelines standards aimed at adapting digital platforms to users with disabilities are considered. Speciali zed tools for automated testing and analysis of various aspects of web page accessibility are outlined. An asses sment of the digital accessibility of the university web resource is given and recommendations for its improvement are given, in terms of accessibility of resources for users with visual, hearing, motor and cognitive impairments.